Study of weed population and growth performance of different rice varieties under aerobic condition / Muhammad Nazhif Mohd Sayuti - Mohd Sayuti, Muhammad Nazhif (Faculty of Plantation and Agrotechnology, 2019)
Rice is a main source of food for more than half of the world population, and more than 90% of rice worldwide is grown and consumed in Asia. Aerobic rice was one of the planting techniques that could overcome water scarcity or drought problems in Malaysia. This is because aerobic rice can be planted in non-puddled and non-saturated condition which reduce water consumption more than 50% compared to irrigated rice. Sustainable weed management strategy in aerobic rice system would be beneficial from both economic and environmental perspectives. However, weed infestation is one of the major limitation in aerobic rice production due to no standing water upon rice germination. Objectives of this study was to identify weed population and rice growth performance under different types of rice varieties. A glass house experiment was conducted to evaluate the competitive ability of three rice varieties, namely AERON 1, MRIA 1, and MR 219 in RCBD with 3 replications. Results revealed that MR 219 had the lowest weed dry weight and weed density and the highest weed dry weight was recorded in AERON 1. Grasses were the most dominant weeds which occupied more than 60% of sum dominance ratio, where Leptochloa chinensis was the most dominant weeds in glass house. MRIA 1 with characteristics of taller plant stature and short growth duration competed better with weed as compared to other varieties with shorter plant and longer growth duration. Weed competition had negative impact on rice plants. Result for plant height showed that MRIA1 had the highest plant height while for the result number of tillers indicated that MR219 had the highest number of tiller then result for leaves chlorophyll revealed that AERON 1 had highest leaves chlorophyll content.